Design of "double layer" texture to obtain superhydrophobic and high wear-resistant PTFE coatings on the surface of Al2O3/Ni layered ceramics. (August 2019) - Fan, Hengzhong; Su, Yunfeng; Song, Junjie; Wan, Hongqi; Hu, Litian; Zhang, Yongsheng
Abstract: Solid lubricating polytetrafluoroethylene (PTFE) coating was designed to have a "double layer" texture after being sprayed on the untextured and textured surface of Al2 O3 /Ni layered ceramics. Surface texture of PTFE coating with smaller diameter and higher density showed excellent superhydrophobicity. Laser caused defluorinated and enhanced hardness of the PTFE coating. Meanwhile, Solid lubricants embedded in micro-dimples of substrate surface act as "mechanical self-locking" roles, which increase the surface contact area and provided a secondary lubricating effect, thus significantly increase the wear life of the coatings. Contact angle and wear life of the optimized "double layer" texture PTFE coatings could reach 160° and 1.6 × 10 4 s, which are about 2.0 and 5.0 times higher comparing to untextured smooth PTFE coatings surface, respectively. Graphical abstract: High-performance alumina matrix ceramic materials play key roles as structural components for aerospace industry because of their excellent mechanical properties and low density, wherein both high oxidation stability. Based on the previous study in which high-performance Al2 O3 /Ni laminated ceramic and surface lubrication structure design, yet another solid lubricating PTFE coating was designed to have a "double layer" texture after being sprayed on the untextured and textured surface of Al2 O3 /Ni layered ceramics. The effects of patterns and geometric parameters of the texture on super-hydrophobicity of the coating were investigated. Influence of "double layer" texture of the substrate and coating surfaces on the wear-resistance and life of the coating were studied as well. Result shown that the texture patterns with controlled sizes and regular shapes can be generated on the PTFE coating sprayed on Al2 O3 /Ni layered ceramics by optimizing laser parameters. Pattern and parameters of the surface textures significantly affect hydrophobicity of PTFE coating surface. Laser treatment caused defluorination of PTFE and decreased content of surface F, which significantly improved surface hardness of the coating. By optimization the "double layer" texture by the laser, PTFE lubricating coatings with excellent super-hydrophobicity and high wear resistance were prepared on the surface of Al2 O3 /Ni layered ceramics.Image 1 Highlights: "Double layer" textures were produced on the surface of PTFE coating and ceramic. The hydrophobic and tribological properties of modified PTFE coatings were studied. Texture have an important influence on the hydrophobic properties of coatings. Laser can cause defluorinated and enhanced hardness of the PTFE coating. Optimized texture surface show excellent superhydrophobic and high wear-resistance.